2019
DOI: 10.1089/cell.2018.0050
|View full text |Cite
|
Sign up to set email alerts
|

Improves theIn VitroDevelopmental Competence and Reprogramming Efficiency of Cloned Bovine Embryos by Additional Complimentary Cytoplasm

Abstract: Somatic cell nuclear transfer (SCNT) is a useful technology; however, its efficiency is low. In this study, we investigated the effects of cytoplasmic transfer into enucleated oocytes on the developmental competence and quality of cloned preimplantation bovine embryos via terminal deoxynucleotidyl transferase dUTP nick-end labeling, quantitative reverse transcription PCR, and immunocytochemistry. We used cytoplasm injection cloning technology (CICT), a new technique via which the cytoplasmic volume of an enucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…Changes in mitochondrial redox state and metabolites have also been associated with changes in histone modification and transcriptome profile (Kopinski et al, 2019). Finally, and further supporting our hypothesis, bovine SCNT blastocysts were recently shown to have a significantly lower mitochondrial mass than expected from the amount of ooplasm removed by enucleation and display increased abundances of DNA methyl transferase (DNMT1 and DNMT3A) transcripts as compared with IVF controls (Xu et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…Changes in mitochondrial redox state and metabolites have also been associated with changes in histone modification and transcriptome profile (Kopinski et al, 2019). Finally, and further supporting our hypothesis, bovine SCNT blastocysts were recently shown to have a significantly lower mitochondrial mass than expected from the amount of ooplasm removed by enucleation and display increased abundances of DNA methyl transferase (DNMT1 and DNMT3A) transcripts as compared with IVF controls (Xu et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…The cellular growth arrest occurring in senescence is seemingly regulated through two main pathways, p16 INK4a -Rb and p53-p21 CIP1 (REF 137 ). Importantly, administration of senolytic agents, which selectively eliminate senescence cells, have been shown to improve physical function and increase longevity in mice 138 .…”
Section: Emerging Areas Of Researchmentioning
confidence: 99%
“…The zonafree embryos can easily transmit diseases and be damaged during handling (Verma et al, 2015). Recently, the CICT method has been developed to overcome the drawbacks of traditional cloning methods (Xu et al, 2019). Using the CICT method, the cytoplasmic volume of enucleated oocytes is restored by donor-cytoplast oocytes.…”
Section: Figmentioning
confidence: 99%
“…In a previous study, the reconstructed cloned embryo, using CICT, showed that gene expression levels of DNMT 1 and DNMT 3a were significantly lower than in the traditional cloning method, indicating that CICT can improve epigenetic reprogramming. (Xu et al, 2019). In this study, we have evaluated the effect of the cytoplasmic volume on acetylation (acH3K9/14 and acH3K56) and apoptosis.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation